Tales of Ogonshoto - Anwar Ridhwan Dato' 1949- (Dewan Bahasa dan Pustaka, 2016)
"Naratif Ogonshoto (Tales of Ogonshoto) by Anwar Ridhwan is one of the modern literary works in Malaysia which provokes the great intrest of the readers as well as the critics. It is traditional and simultaneously modern and international in nature. The author succeeds to change the character of literature as a mere story to make it as a drama of intellectual searchings. Archipelago of Ogonshoto, though very small and situated very far from the rest of the world, thanks to the talent of the author becomes a region where all the problems nowadays confronted by the humanity can be found: democracy, dictatorship, poverty, ecology, morality, cruelty, the role of mass media etc. and in spite of all symbolism and mystics of the fiction, everything which is happening with the heroes is fed by the reality of the world. Tales of Ogonshoto can be considered as a warning against the future tragedy faced by the humanity of the world, tragedy caused by the cruelty in the blood of the people"